The potential of a stratified ontology for developing materials in community-based coastal marine environmental education processes - Davies, Siân May (Rhodes University, Faculty of Education, Department of Education, 2009)
This study set out to explore the possibilities that the Critical Realist concept of a stratified ontology might have for environmental learning and materials development processes. This involved processes of ongoing contextual profiling; the use of picture-based resources and storytelling to support the engagement with the marine harvesting contexts of the villages of Hamburg and Ngqinisa, in the former Ciskei. At the heart of the study was the process of uncovering the empirical, the actual and the real in the context of a community of coastal marine harvesters whose lives and livelihoods are affected by poverty and a history of inequality, and more recently by issues such as HIV/AIDS. Their stories of existing practice changed as we engaged with picture-based narratives, gaining depth and focus in relation to sustainability issues. The learning processes associated with and emerging out of the research processes were enhanced through abductive use of metaphors and graphic illustrations, and through intra- and inter community exchanges, again using picture based narratives. As the study unfolded, the development of environmental education materials receded. Focus turned to how conceptual abstraction processes (of abduction (metaphor) and retroduction) and the stratified ontological framework allowed for learning across epistemological divides.
Keywords: Ontology; Critical realism; Environmental education -- South Africa -- Eastern Cape; Sustainable development -- South Africa -- Eastern Cape; Community-based conservation -- South Africa -- Eastern Cape; Marine resources development -- South Africa -- Eastern Cape; Marine ecology -- Study and teaching -- South Africa -- Eastern Cape; Teaching -- Aids and devices -- South Africa; Poor -- Education -- South Africa